The cellular basis of bioadhesion of the freshwater polyp Hydra. Issue 1 (December 2016) - Rodrigues, Marcelo; Leclère, Philippe; Flammang, Patrick; Hess, Michael; Salvenmoser, Willi; Hobmayer, Bert; Ladurner, Peter
Abstract Background The freshwater cnidarianHydra temporarily binds itself to numerous natural substrates encountered underwater, such as stones, leafs, etc. This adhesion is mediated by secreted material from specialized ectodermal modified cells at the aboral end of the animal. The means by whichHydra polyps attach to surface remain unresolved, despite the fact that Hydra is a classic model in developmental and stem cell biology. Results Here, we present novel observations on the attachment mechanism ofHydra using high pressure transmission electron microscopy, scanning electron microscopy, atomic force microscopy, super-resolution microscopy, and enzyme histochemistry. We analyzed the morphology of ectodermal basal disc cells, studied the secreted material, and its adhesive nature. By electron microscopy we identified four morphologically distinct secretory granules occurring in a single cell type. All the secretory granules contained glycans with different distribution patterns among the granule types. Footprints of the polyps were visualized under dry conditions by atomic force microscopy and found to consist of a meshwork with nanopores occurring in the interstices. Two antibodies AE03 and 3G11, previously used in cell differentiation studies, labelled both, basal disc cells and footprints. Our data suggest that the adhesive components ofHydra are produced, stored and delivered by a single cell type. Video microscopy analysis corroborates a role of muscle contractions for the detachment process. Conclusion We clearly demonstrated that bioadhesion ofHydra relies on the secreted material. Our data suggest that glycans and/or glycoproteins represent an important fraction of the secreted material. Detachment seems to be initiated by mechanical forces by muscular contractions. Taken together, our study represents the characterization of an unique temporary adhesive system not known in aquatic organisms from other metazoan phyla.